TRANSFORMATIONAL LEADERSHIP STYLE OF MANAGEMENT AND ISSUES OF ITS EFFECTIVE USE. - Narimonov Nuriddin Narimon o‘gʻli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article provides an in-depth analysis of the transformational leadership style, which is widely used in modern management, and its impact on management effectiveness. The theoretical foundations of transformational leadership, its structural elements, and forms of application in management practice are highlighted. The author has studied in detail the factors affecting the effective use of the transformational style by managers, in particular, the personal qualities of the leader, organizational culture, and issues related to employee motivation. The article presents the impact of this leadership style on the development of the enterprise, its importance in increasing employee efficiency, and practical recommendations for solving current problems.